Incidental vocabulary acquisition from listening to stories: a comparison between read-aloud and free storytelling approaches. Issue 5 (28th May 2018) - Lenhart, Jan; Lenhard, Wolfgang; Vaahtoranta, Enni; Suggate, Sebastian
Abstract: Shared-book reading is a well-established intervention to foster vocabulary development. Factors influencing its effectiveness are, however, less well studied, particularly with regard to story-delivery. We contrasted a read-aloud with a free storytelling approach and tested effects on vocabulary learning. In the first study, 83 preschoolers aged three to six were told six stories in a randomised, single-blind and counterbalanced design. Stories were either read aloud or told freely and included rare target-words. Measures of target-word acquisition, receptive vocabulary, phonological working memory and speech comprehension were administered. There was a small to moderate learning gain ( d  = .37), but no effect of story-delivery. In a second study, 24 of the youngest and 24 of the oldest participants were tested again, using the same procedure but with stories designed to be more intrinsically motivating and age-appropriate. Results indicated negligible vocabulary gains ( d  = .08) and no effect of story-delivery, except for small differences in child behaviour during storytelling.